Bowel obstruction due to small bowel fistulization seven years after magnet ingestion: a case report - Chloe Savino; Kristen Calabro (Journal of Pediatric Surgery Case Reports)
Introduction: Accidental ingestion of magnets by children is known to cause complications in the acute period, including tissue necrosis, perforation, obstruction, and fistulization. There are limited case reports in the literature describing complications several years after the initial ingestion of the magnet. Case presentation: A 17-year-old male with autism spectrum disorder presented with 1 day of abdominal pain and several episodes of emesis. On exam, he was distended and tender to palpation in the lower abdomen. Blood tests were notable for leukocytosis of 21.4 thousand/ul. A computerized tomography (CT) of the abdomen and pelvis without contrast showed evidence of a small bowel obstruction possibly with a transition point involving an ileal loop in the mid-abdomen. Given the fact that the patient had no previous abdominal operations, he was taken to the operating room for a diagnostic laparoscopy. We found an entero-enteric fistulous tract that was causing a closed loop obstruction through an internal hernia in the mid jejunum. The bowel was healthy and viable. Using a single fire of a stapler, the fistulous track was divided in a transverse fashion, freeing the loops connected by it. Upon further investigation, the patient's parents recalled that the patient had ingested three magnets seven years prior that passed within 24 hours with no known complications at the time. The patient had an uncomplicated recovery, with return of bowel function on post-operative day 1 and was discharged home on post-operative day 2. Conclusion: Fistulas from magnet ingestion can present years after the inciting event with symptoms of bowel obstruction due to an internal hernia and may require urgent surgical intervention.